Pendekatan Rule Of Reason Dan Per Se Illegal Dalam Perkara Persaingan Usaha - Wihelmus Jemarut (Universitas Widya Gama Malang, 2020)
Commission for Business Competition Supervision (Komisi Pengawas Persaingan Usaha or KPPU) is an institution established to deal with issues related to business competition and monopoly practices. This article wants to describe the approaches to be taken by KPPU in dealing with the business competition cases. This research employed a normative research method with conceptual and case approaches. The result of research showed that there are two approaches to dealing with business competition case: rule of reason and per sel illegal. These two approaches can be selected alternatively, but they can also be used concomitantly. Rule of reason approach trials the substance of business action and its effect on community economy, while the per se illegal approach uses juridical positivistic approach. Keywords: Business Competition, Per se Illegal, Rule of Reason